Realisation of ethics in the activity of a social worker - Leliūgienė, Irena; Andrijevska, Violeta; Kaušylienė, Angelė (Social Welfare: Interdisciplinary Approach, 2016)
The article presents the results of the research in the realisation of ethics in social work activities. Social work is a complex and multifaceted profession in which  practice is based on strong values. Social work values and ethical principles have been a particularly acute and debatable topic since ancient times.  It has always been noticed that social work practical activities raise ethical issues and dilemmas. Ethical problems and their solutions are basic problems in the development of social work as a profession. Due to these reasons, the main goal of this article was set: to reveal how ethics are implemented by social workers in practice. In order to achieve the goal, the following objectives were set: 1.  to explore the concept of ethics and values in social work context. 2.  to analyse how the social worker's ethical standards are being implemented in various fields of activity. 3.  to examine how ethics is realised in practice by the social workers of N District Municipality. In order to achieve the goal and tasks,  the concept of ethics and values in social work was discussed as well as the analysis of social work ethics  was implemented in various branches and spheres of activity. To reveal the topic, the research (survey) was carried out, which was attended by the N District Municipality social workers. Closed-ended questions were analysed by quantitative research methods and open-ended questions were processed by qualitative research methods. The results revealed that social workers of  N District Municipality knew the ethical standards of their profession and implemented them in all the mentioned aspects of ethical codes. Social workers identified five main reasons which cause violations of ethical standards in their practice: apathy of colleagues, heavy workload, lack of offices,  problematic clients and nervous tension at work.
Keywords: ethical standards; ethical problem; social work; social work ethics; social worker